2021
DOI: 10.3390/v13050899
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic SARS-CoV-2 Reinfection in a Healthy Healthcare Worker in Italy Confirmed by Whole-Genome Sequencing

Abstract: This study describes a case of SARS-CoV-2 reinfection confirmed by whole-genome sequencing in a healthy physician who had been working in a COVID-19 hospital in Italy since the beginning of the pandemic. Nasopharyngeal swabs were obtained from the patient at each presentation as part of routine surveillance. Nucleic acid amplification testing was performed on the two samples to confirm SARS-CoV-2 infection, and serological tests were used to detect SARS-CoV-2 IgG antibodies. Comparative genome analysis with wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The shortest time from first infection to reinfection was 19 days [59] and the longest was 293 days [71].…”
Section: Time From First To Second Clinical Symptommentioning
confidence: 98%
“…The shortest time from first infection to reinfection was 19 days [59] and the longest was 293 days [71].…”
Section: Time From First To Second Clinical Symptommentioning
confidence: 98%
“…We restricted our search to publications in English. As of June 5, 2021 only six publications confirmed the hypothesis of reinfection (Adrielle Dos Santos et al 2021;Gupta et al 2020;Selhorst et al 2020;Loconsole et al 2021;Brehm et al 2021) through whole-genome sequencing, however not all have shown distinct variants for both infection episodes (Table S1).…”
Section: Evidence Before This Studymentioning
confidence: 99%
“…However, since only one patient in 25 was infected, wearing a surgical mask could be also considered useful. Compared with the general population, HCWs are at higher risk of repeated exposure to SARS-CoV-2 infection in hospital settings and, despite the use of personal protective equipment such as ffp2 masks, face shields, double gloves, and gowns, reinfection and nosocomial outbreaks caused by wild-type and Alpha strains of SARS-CoV-2 have occurred [20,21]. Because Omicron VOC is three-to sixfold more infectious than previous variants [33], measures of infection control in non-COVID-19 wards require strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…For each positive sample, the cycle threshold (Ct) values were recorded for all three genes as an indirect index of viral load and a valuable proxy for infectious virus [19,20]. Additionally, whole-genome sequencing (WGS) was performed using the Ion Torrent platform (ThermoFisher Scientific, Waltham, MA, USA), as previously described [21]. Phylogenetic analysis was performed using the Nextclade sequence analysis webapp (https://clades.nextstrain.org/, accessed on 14 February 2021).…”
Section: Methodsmentioning
confidence: 99%